Validation of Inner Magnetosphere Particle Transport and Acceleration Model (IMPTAM) With Long‐Term GOES MAGED Measurements of keV Electron Fluxes at Geostationary Orbit. Issue 5 (16th May 2019) - Ganushkina, N. Yu; Sillanpää, I.; Welling, D.; Haiducek, J.; Liemohn, M.; Dubyagin, S.; Rodriguez, J. V.
Abstract: Surface charging by keV (kiloelectron Volt) electrons can pose a serious risk for satellites. There is a need for physical models with the correct and validated dynamical behavior. The 18.5‐month (2013–2015) output from the continuous operation online in real time as a nowcast of the Inner Magnetosphere Particle Transport and Acceleration Model (IMPTAM) is compared to the GOES 13 MAGnetospheric Electron Detector (MAGED) data for 40, 75, and 150 keV energies. The observed and modeled electron fluxes were organized by Magnetic Local Time (MLT) and IMPTAM driving parameters; the observed Interplanetary Magnetic Field (IMF) B Z, B Y, and | B |; the solar wind speed V S W ; the dynamic pressure P S W ; and Kp and SYM‐H indices. The peaks for modeled fluxes are shifted toward midnight, but the ratio between the observed and modeled fluxes at around 06 MLT is close to 1. All the statistical patterns exhibit very similar features with the largest differences of about 1 order of magnitude at 18–24 MLT. Based on binary event analysis, 20–78% of threshold crossings are reproduced, but Heidke skill scores are low. The modeled fluxes are off by a factor of 2 in terms of the median symmetric accuracy. The direction of the error varies with energy: overprediction by 50% for 40 keV, overprediction by 2 for 75 keV, and underprediction by 18% for 150 keV. The revealed discrepancies are due to the boundary conditions developed for ions but used for electrons, absence of substorm effects, representations of electric and magnetic fields which can result in not enough adiabatic acceleration, and simple models for electron lifetimes. Key Points: IMPTAM performs well, with the ratio between the GOES MAGED and modeled keV electron fluxes at 06 MLT close to 1 Peaks of IMPTAM fluxes are shifted toward midnight due to the background field models and the sources and losses used inside IMPTAM Error is a factor of 2 based on median symmetric accuracy with largest difference of 1 order of magnitude; Heidke skill scores are low